Пространственное изучение Немировского городища - Дараган, М.Н.; Разумов, С.Н.; Снытко, Н.И.; Бондарь, К.М.; Вершило, И.В. (Археологічні дослідження в Україні, 2010)
In 2009, the works started on spatial research of Nemyriv hill-fort of the 8th—7th c. BC. A detailed tacheometric survey was conducted of defense fortifications of the hill-fort and the development was started of their 3-dementional models. A geomagnetic survey was conducted of an area at the site.